Burmannia munnarensis (Burmanniaceae) a new species and rediscovery of B. indica after 110 years from southern Western Ghats, Kerala, India - Francis, Dani; Mohan, Vishnu; Venugopal, Divya K.; Nampy, Santhosh (Phytotaxa, 2021)
A new species of Burmannia (Burmanniaceae), endemic to the southern Western Ghats of Kerala, India is described as Burmannia munnarensis and illustrations are provided. The new species is morphologically most similar to B. indica but can be easily distinguished by its narrow flower wings, involute margin of the perianth lobes, shorter perianth tube and shape of inflorescence. Burmannia indica, known only from the type locality Peermade in Idukki district, Kerala, is rediscovered after a lapse of 110 years on another locality, Meenuliyanpara in the same district. Key to the Indian species of Burmannia is included and status of both taxa is provisionally assessed as per IUCN Red List Categories and Criteria.